Supported Binuclear Gold Phosphine Complexes as CO Oxidation Catalysts: Insights into the Formation of Surface‐Stabilized Au Particles - Fabian Rang; Tim Delrieux; Florian Maurer; Franziska Flecken; Jan‐Dierk Grunwaldt; Schirin Hanf (Small Science)
Atomically precise gold phosphine complexes as precursors for supported Au catalysts tested in CO oxidation are presented. Using a variety of analytical techniques, including in situ and operando X‐ray absorption spectroscopy, it is discovered that minor changes in the ligand of the molecular complexes result in significantly different activation behaviors of supported Au catalysts under reaction conditions. When using [Au2(μ2‐POP)2]OTf2 (POP = tetraphenylphosphoxane) as single‐source precursor, an active supported oxidation catalyst in second light‐off is obtained, outperforming a commercial Au/TiO2 and a P‐free Au/Al2O3 reference catalyst. Conversely, using [Au2(μ2‐dppe)2]OTf2 (dppe = diphenylphosphinoethane) on alumina leads to a significant decrease in CO oxidation activity. This difference is attributed to the formation of P‐containing ligand residues on the support in the case of [Au2(μ2‐POP)2]OTf2/Al2O3, which enhances the thermal stability of the Au particles and affects the particle's electronic properties through charge transfer processes. This work provides insights into the dynamic ligand decomposition of molecular gold complexes under reaction conditions and demonstrates the delicate balance between the stabilization of Au particles, clusters, and complexes using ligands and the blocking of active sites. This knowledge will pave the way for the targeted use of molecular transition metal complexes as precursors in synthesizing surface‐stabilized nanoparticles.